Exchangeable basic cations and nitrogen distribution in soil as affected by crop residues and nitrogen - Rosolem, Ciro Antonio [UNESP] (Brazilian Archives of Biology and Technology, 2011)
In this work, a greenhouse experiment was conducted to study the effects of N fertilization and residues of pearl millet, black oats and oilseed radish on pH and Ca, Mg, K, NO3-, and NH4+ distribution within the profile of a Distroferric Red Latosol. The equivalent of 8 t ha-1 of plant residues were placed on soil surface. Lime was applied on the soil surface and nitrogen was applied over the straw at 0, 50, 100, and 150 mg kg-1, as ammonium nitrate. Corn was grown for 57 days. Calcium contents and pH in the soil profile were decreased by Pearl millet residue, while black oat and oilseed radish increased Ca contents and these effects are not related with Ca contents in residue tissue. However, the presence of plant residues increased nitrate, ammonium, and potassium contents in the deeper layers of the pots.
Keywords: Calcium; magnesium; nitrogen; potassium; soil bases; no till